Relaparotomy in residual ovarian syndrome: an appraisal - Shrestha, Prezma; Rawal, Suniti Joshi; Sharma, Nisha (Journal of Chitwan Medical College, 2020)
Background: Hysterectomy is one of the most commonly performed surgical procedures among females, usually accompanied by unilateral or bilateral salpingo-oophorectomy. Women tend to preserve normal ovary as its removal is associated with higher risks of cardiovascular diseases, osteoporosis, neuro-psychiatric disorders, colorectal and lung cancer. However, preservation of ovary during hysterectomy may increase risk of relaparotomy for residual ovarian syndrome. This study aimed to evaluate the clinical, intraoperative and histopathological characteristics of ROS. Methods: This was a retrospective study done in the Department of Obstetrics and Gynecology, TUTH. Seventeen cases of ROS that were identified to have undergone relaparotomy from year April 2015 to March 2020 were studied. Review of documents was done to find out the cause of hysterectomy and preservation of ovaries. Operative/pathological characteristics of mass along with operative complications were accessed. Data was entered and descriptive analysis was done in SPSS 24 software. Results: Total of 17 patients who underwent relaparotomy for ROS was identified. Most common presentation was abdominal pain(53%) and most patient(41%) presented with ROS within five years of hysterectomy. Pelvic adhesions were seen in almost 94% of the cases. One case sustained bladder injury. However, DJ stenting was done in 4 cases as precaution. Eighty two percent mass were benign in nature whereas 18% were malignant. Conclusions: Relaparotomy in cases with ROS has a vital role. Though intraoperative complications like adhesions are encountered, it helps to diagnose the pathology of the symptomatic residual mass for the further management of the case.